2007
DOI: 10.1093/jn/137.5.1200
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Induces Mast Cell Recruitment during Mouse Mammary Gland Stromal Remodeling1

Abstract: Conjugated linoleic acid (CLA) is a dietary chemopreventive agent that induces apoptosis in the mammary adipose vascular endothelium and decreases mammary brown adipose tissue (BAT) and white adipose tissue (WAT). To determine onset and extent of stromal remodeling, we fed CD2F1/Cr mice diets supplemented with 1 or 2 g/100 g mixed CLA isomers for 1-7 wk. BAT loss, collagen deposition, and leukocyte recruitment occurred in the mouse mammary fat pad, coincident with an increase in parenchymal-associated mast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, we found calretinin positivity in stromal cells of the lesion, which were mast cells, possibly involved in the remodeling of mammary tissue. 16,17 Therefore, immunostaining with calretinin might have utility on this respect. In syringocystadenoma papilliferum, the luminal epithelial cell layer lining the papillary structures and the tubules shows unequivocal signs of decapitation secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found calretinin positivity in stromal cells of the lesion, which were mast cells, possibly involved in the remodeling of mammary tissue. 16,17 Therefore, immunostaining with calretinin might have utility on this respect. In syringocystadenoma papilliferum, the luminal epithelial cell layer lining the papillary structures and the tubules shows unequivocal signs of decapitation secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In a transplantable mouse model with mammary tumor and spontaneous lung metastasis, CLA [mixture of isomers: c9,t11-CLA (32.5 g/ 100 g), t10,c12-CLA (33.5 g/100 g), 18:1 (18 g/100 g), and other isomers (16 g/100 g)] reduced the metastasis rate, total tumor burden, and the survival of metastatic cells, in a dosedependent manner, without affecting primary tumor growth (130). However, several other studies have demonstrated no effect of c9,t11-CLA, particularly on latency in mice bearing mammary tumors (130)(131)(132)(133). Data from cell culture studies have demonstrated antiproliferative effects of CLA in MCF-7 breast cancer cells (134,135), possibly due to effects on PPARg and E-cadherin/b-catenin pathways (136).…”
Section: Review Of Animal and Cell Culture Studiesmentioning
confidence: 99%
“…It was expected that the 10,12-CLA isomer would specifically induce an increase in mast cell number or differentiation, based on the previous observation that this CLA isomer significantly increases mast cell abundance in the mouse mammary gland (Russell et al, 2007). We hypothesized that the effects of CLA may be directly mediated through its effects on mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have found their abundance increased in mouse mammary gland specifically in response to feeding with trans10,cis12-CLA (10,12-CLA), coincident with fibrosis and leukocyte recruitment (Russell et al, 2007). This in vivo effect was specific to 10,12-CLA and not seen with cis9,trans11-CLA (9,11-CLA).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation